The phytochemical analysis and pharmacological potentials of husk and straw as paddy waste products. (22nd April 2020) - Murtey, Mogana Das; Seeni, Azman
Abstract: Rice serves as a staple food for one‐half of the global population. However, rice production, particularly the rice milling process, results in a substantial amount of paddy waste products (e.g. bran, husk and straw) annually. Because the potentials of bran have been extensively explored in prior studies, the present review focuses exclusively on the phytochemical analysis and pharmacological potentials of husk and straw. This comprehensive review establishes a solid foundation for promoting husk and straw as medicinal substances given their promising pharmacological potentials as bioactive compound sources with therapeutic functions. © 2020 Society of Chemical Industry